The best of enemies : race and redemption in the new South - Davidson, Osha Gray (The University of North Carolina Press, 2007)
The author of Broken Heartland and Under Fire describes how C.P. Ellis grew up amid the racism and poverty of the South, his association with the Ku Klux Klan, and his first meeting and growing friendship with civil-rights activist Ann Atwater. 15,000 fi.